THE INFLUENCE OF EDUCATION AND JOB TRAINING ON THE WORK COMPETENCE OF EMPLOYEES AT THE FISHERIES AND FOOD SERVICE OF TANAH DATAR REGENCYTHE INFLUENCE OF EDUCATION AND JOB TRAINING ON THE WORK COMPETENCE OF EMPLOYEES AT THE FISHERIES AND FOOD SERVICE OF TANAH DATAR REGENCY - Puspita, Asma Devi; Putra, Dedelfi; Aima, M. Havidz; Fitriyeni, Fitriyeni (Gapenas Publisher, 2025)
This study aims to determine the effect of education and job training on employee competency at the Tanah Datar Regency Fisheries and Food Service. Employee competency is an important factor in supporting the achievement of public sector organizational performance. Education and job training are strategic efforts undertaken by organizations to improve employee capabilities, knowledge, and skills so they can carry out their duties effectively and efficiently. This study uses a quantitative approach with a survey method. The population in this study were all employees of the Tanah Datar Regency Fisheries and Food Service, with samples taken using a purposive sampling technique. Data collection was carried out by distributing questionnaires that had been tested for validity and reliability. The data analysis technique used was multiple linear regression. The results of the study indicate that education and job training have a positive and significant effect on employee competency. This finding indicates that the higher the quality of education and the more frequent job training provided, the better the employee competency. Therefore, organizations are advised to continue to improve targeted and sustainable education and training programs to create superior and professional human resources.